Screening and production of bioplastic (PHAs) from sugarcane rhizospheric bacteria - Simanta1, Shukla Aparna1, Shukla Kamlesh2, Gupta Shraddha1, *Rajput Yogita1, Shit (International Multidisciplinary Research Journal, 2011)
There has been considerable interest in the development and production of biodegradable polymer to solve the current problem of pollution caused by the continuous use of synthetic polymer of petroleum origin. Polyhydroxyalkanoates (PHAs) are known to be accumulated as intracellular inclusion in some bacteria. The materials properties exhibited by PHAs, ranging from stiff, brittle to rubber-like makes it a close substitute for the synthetic plastic. Under this study, ten bacteria were isolated from sugarcane rhizosphere sample collected from Pacheda, Raipur (Chhattisgarh). Isolates were grown in the production media containing high carbon concentration. Out of ten bacteria, only six bacteria produce PHA i.e. Micrococcus luteus 2, Micrococcus mucilaginosus, Micrococcus nishinomiyaensis, Micrococcus radiodurans, Streptococcus equinus, Streptococcus raffinolactis. Out of which, Micrococcus mucilaginosus and Streptococcus raffinolactis produce high amount of PHA. Because of their special characteristics and broad biotechnological applications, it can be industrially exploit for bioplastics production.